Prayer as performance, c.1050-1250 - Lindstedt, S (2021)
This thesis examines manuscripts of prayer texts produced in England between 1050-1250, considering how aspects of their material context influence the function, significance, and performance of personal devotion. In so doing, it intends to reconstruct the experience of engaging with these texts and understand how medieval interpretations of the meaning and purpose of prayer might differ from our own. Using Gerard Genette’s definition of ‘paratexts’ to refer to features of the page that are external but integral to a literary text, it considers how paratextual features can suggest performance directions, uses, or appropriate times and places for a particular prayer to its user. Its close reading demonstrates that prayer texts are rarely presented unpackaged to their users but are often shaped by instructive rubrics and punctuation that dictate their function and performance. While the virtual ubiquity of such paratexts in devotional manuscripts indicates their importance to their correct use, they are not always accurately represented in critical editions or incorporated into interpretations of prayer texts. Integrating paratextual features into critical readings of devotional texts allows this thesis to present a fuller and more accurate picture of the methods and effects of the piety they were crafted to inspire, showing that reading around a text can be as valuable and as meaningful as reading into it. The consistent connection of devotional paratexts with the performance of prayer, in setting out the contexts, intentions, and methods associated with a particular text, further illustrates that contemporary audiences approached prayer as an activity, contrasting with its modern perception as an exclusively internalised experience.